Bildgebende UV/VIS-Spektroskopie zur Untersuchung des Einflusses der Fluiddynamik auf die Entstehung von Haupt- und Nebenprodukt in schnellen konkurrierenden konsekutiven Gas-Flüssig-Reaktionen - Felix Kexel and Alexandra von Kameke and Martin Oßberger and Marko Hoffmann and Peter Klüfers and Michael Schlüter (Chemie - Ingenieur - Technik, 2020)
To form many bulk chemicals, gaseous substances must be mixed and reacted with a continuous liquid phase. In this research work, we systematically investigate to what extent the formation of a side product in a fast competing consecutive reaction can be influenced by the time scales of mixing. For this purpose, a Taylor bubble experiment is used, in which the time scales of mixing can be varied systematically and reproducibly. It is shown, that the mixing in the wake of a bubble is of great importance for the formation of by-products.
Keywords: Gas-liquid reactions; Mass transfer phenomena; Reactive bubbly flows; Taylor bubble; UV/VIS-Spectroscopy